Approximation by entire functions in the mean on the real axis - Stepanets , A. I.; Stepanets , N. I. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Approximations in a locally integral norm of functions representable as a convolution on the whole line by means of Fourier operators are studied.